Biodegradable materials, methods of making, uses, and degradable stents

CN118022072BActive Publication Date: 2026-10-09FUDAN UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211384250.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-07
Publication Date
2026-10-09
Estimated Expiration
2042-11-07

AI Technical Summary

Technical Problem

这类材料已在临床上得到广泛应用和认可,但仍存在如下不足:(1)其机械强度远低于金属材料,并且存在降解过程力学性能损失过快的问题;(2)这类材料属于热塑性高分子材料,在外力作用下普遍存在力学松弛行为,易导致器械产品在储存运输过程中力学性能逐渐丧失,产品货架储存期短,产品质量稳定性较差;(3)降解速率与其应用领域的降解周期要求无法合理匹配

Benefits of technology

[0043]The raw materials for preparing the aforementioned biodegradable materials include high-molecular-weight biodegradable polyesters and low-molecular-weight macromonomers. The acidic products generated by the degradation of the relatively fast-degrading macromonomers can be designed to catalyze the in-situ degradation of the slower-degrading biodegradable polyester. Simultaneously, the overall crystallinity of the material can be controlled by adjusting the amount of macromonomers added, making the degradation cycle of the biodegradable polyester material controllable. Furthermore, the biodegradable polyester and macromonomers form a chemically cross-linked network with a certain content and a spherulitic physical network with a certain degree of crystallinity. This allows the biodegradable material to have a controllable degradation cycle while maintaining good structural stability and not reducing mechanical properties, or even improving them. It can be used in fields such as vascular stents, cardiac occluders, surgical sutures, tissue packing materials, bone repair products, and food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118022072B_ABST
    Figure CN118022072B_ABST
Patent Text Reader

Abstract

The application relates to a biodegradable material and a preparation method, application and degradable support thereof. The biodegradable material has a chemical cross-linking network and a spherulite physical network. The content of the chemical cross-linking network of the biodegradable material is 20-100%, and the crystallinity is 5-50%. The preparation raw material of the biodegradable material comprises degradable polyester and a macromolecular monomer. The number average molecular weight of the degradable polyester is greater than or equal to 100,000. The macromolecular monomer comprises a multi-arm degradable polyester prepolymer with a carbon-carbon double bond at the end group. The chemical cross-linking network comprises a chemical cross-linking network formed by macromolecular monomer cross-linking, a chemical cross-linking network formed by covalent bond connection between the macromolecular monomer and the degradable polyester and a chemical cross-linking network formed by covalent bond connection between the degradable polyester. The spherulite physical network comprises a crystalline network formed by the degradable polyester. The biodegradable material has a controllable degradation period, excellent structural stability and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a biodegradable material, its preparation method, application, and biodegradable scaffold. Background Technology

[0002] Biodegradable polymers are a class of materials that can be gradually degraded and absorbed in biological organisms or in vitro environments, ultimately transforming into carbon dioxide and water, which then enter the circulatory system. These include biodegradable natural polymers and biodegradable synthetic polymers. Among these, biodegradable synthetic polymers are widely used in fields such as biomedicine and medical devices, and food packaging due to their wide availability, excellent overall performance, strong design flexibility, and reliable biosafety. Examples include drug delivery systems, vascular stents, cardiac occluders, coating materials, absorbable surgical sutures, tissue packing and anti-adhesion, and other tissue repair applications in biomedicine and medical devices, as well as biodegradable food packaging bags in the food packaging field.

[0003] The most commonly used biodegradable synthetic polymers include polylactic acid, polycaprolactone, polyglycolic acid, polytrimethylene carbonate, polybutylene succinate, polydioxanone, and other polymers and their copolymers or blends. These materials have been widely used and recognized in clinical practice, but they still have the following shortcomings: (1) Their mechanical strength is much lower than that of metal materials, and there is a problem of rapid loss of mechanical properties during the degradation process; (2) These materials are thermoplastic polymers, and they generally exhibit mechanical relaxation behavior under external forces, which can easily lead to the gradual loss of mechanical properties of medical devices during storage and transportation, resulting in short shelf life and poor product quality stability; (3) The degradation rate cannot be reasonably matched with the degradation cycle requirements of their application fields.

[0004] In the field of medical device applications, the mechanical properties, structural stability, and degradation cycle of the aforementioned polyester biodegradable materials are three important performance indicators that play a crucial role in whether the device product can fulfill its function. Excellent mechanical properties often determine the effectiveness of treatment. For example, in biodegradable coronary stents, insufficient radial support or rapid loss can lead to adverse events such as restenosis or stent breakage before being covered by the endothelium. Stents with high radial support typically have lower lumen loss and restenosis rates, while insufficient stent toughness can easily lead to stent breakage, demonstrating the importance of mechanical properties. Linear polymer materials generally exhibit relaxation or creep behavior under external conditions, causing changes in the internal chain structure of polyester materials. This typically affects the mechanical stability, shelf life, and safety of the device product; therefore, maintaining the structural stability of the material is extremely important. An appropriate degradation cycle can better match the repair process of tissues or organs, maximizing treatment effectiveness. Furthermore, the degradation cycle plays a vital guiding role in clinical trials and observational endpoints. Generally, under the premise of achieving the same therapeutic effect, a shorter degradation cycle results in lower clinical trial costs and lower risks. However, currently widely used biodegradable polyester materials struggle to simultaneously achieve controllable degradation cycles, improved structural stability, and even enhanced mechanical properties. Traditional technologies improve specific properties of polyester biodegradable materials through various means, but this usually results in a significant decline in other properties, making it difficult to simultaneously improve and enhance multiple properties. Summary of the Invention

[0005] Therefore, it is necessary to provide a biodegradable material and its preparation method that has a controllable degradation cycle, excellent structural stability, and does not reduce or even improve mechanical properties.

[0006] In addition, it is necessary to provide an application of biodegradable materials and a biodegradable scaffold.

[0007] A biodegradable material having a chemical cross-linked network and a spherulite physical network, wherein the content of the chemical cross-linked network of the biodegradable material is 20% to 100%, and the crystallinity is 5% to 50%;

[0008] The raw materials for preparing the biodegradable material include: biodegradable polyester and macromolecular monomers, wherein the number average molecular weight of the biodegradable polyester is ≥100,000, and the macromolecular monomers include multi-arm biodegradable polyester prepolymers with end-group modified carbon-carbon double bonds.

[0009] The chemical crosslinking network includes a chemical crosslinking network formed by the crosslinking of the macromolecular monomers, a chemical crosslinking network formed by the covalent bonding of the macromolecular monomers and the biodegradable polyester, and a chemical crosslinking network formed by the covalent bonding of the biodegradable polyester.

[0010] The spherulite physical network includes the spherulite network formed by the crystallization of the biodegradable polyester.

[0011] In one embodiment, the raw materials for preparation satisfy any one or two of the following conditions:

[0012] (1) In the raw materials used for preparation, the biodegradable polyester comprises 30% to 99% by mass and has a number-average molecular weight of 100,000 to 1,000,000; and

[0013] (2) In the raw materials for preparation, the mass percentage of the macromolecular monomer is 1% to 70%, the number of arms is 2 to 12, and the number average molecular weight of the single arm is 100 to 50,000.

[0014] In one embodiment, the degradation cycle of the biodegradable material is between 1 month and 5 years, the tensile strength is between 20 MPa and 200 MPa, and the elongation at break is between 3% and 200%.

[0015] In one embodiment, the content of the chemical cross-linked network of the biodegradable material is 50% to 90%, and the crystallinity is 20% to 50%.

[0016] In one embodiment, the raw materials for preparation satisfy any one or two of the following conditions:

[0017] (1) In the raw materials used for preparation, the biodegradable polyester accounts for 70% to 95% by mass and has a number-average molecular weight of 200,000 to 500,000; and

[0018] (2) In the raw materials for preparation, the mass percentage of the macromolecular monomer is 5% to 30%, the number of arms is 2 to 6, and the number average molecular weight of the single arm is 5,000 to 20,000.

[0019] In one embodiment, the degradation cycle of the biodegradable material is between 6 months and 3 years, the tensile strength is between 50 MPa and 180 MPa, and the elongation at break is between 3% and 50%.

[0020] In one embodiment, the biodegradable polyester and the multi-arm biodegradable polyester prepolymer are each independently selected from one or more of poly-L-lactide, poly-D-lactide, polyglycolic acid, and poly-ε-caprolactone; or, the biodegradable polyester and the multi-arm biodegradable polyester prepolymer are each independently selected from copolymers formed by copolymerizing at least two monomers selected from D,L-lactide, D-lactide, L-lactide, glycolide, ε-caprolactone, δ-valerolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, butylene succinate, p-dioxanone, and trimethylene carbonate.

[0021] A method for preparing a biodegradable material includes the following steps:

[0022] A biodegradable polyester, a macromonomer, and a first initiator are mixed and then subjected to a crosslinking reaction. The mixture is then cooled at a rate of 1°C / min to 50°C / min to below the glass transition temperature of the biodegradable polyester to prepare a biodegradable material. The crosslinking reaction temperature is between the crystallization temperature and the melting temperature of the biodegradable polyester.

[0023] The biodegradable polyester has a number-average molecular weight ≥ 100,000, and the macromonomer includes a multi-arm biodegradable polyester prepolymer with end-group modified carbon-carbon double bonds.

[0024] In one embodiment, with the total mass of the biodegradable polyester and the macromonomer being 100%, the mass percentage of the biodegradable polyester is 30% to 99%, and the first initiator accounts for 0.05% to 5% of the total mass of the biodegradable polyester and the macromonomer.

[0025] In one embodiment, the first initiator is a photoinitiator, and the crosslinking reaction step includes: ultraviolet light irradiation at 120°C to 200°C for 1 min to 30 min; or,

[0026] The first initiator is a thermal initiator, and the crosslinking reaction step includes: carrying out the crosslinking reaction at 120℃~200℃ for 1min~30min; or,

[0027] The cross-linking reaction steps include: performing an electron beam, X-ray, or γ-ray irradiation cross-linking reaction at 120℃ to 200℃ for 1 min to 30 min.

[0028] In one embodiment, the cooling rate is 5°C / min to 20°C / min.

[0029] In one embodiment, a crosslinking agent is also added in the step of mixing the biodegradable polyester, the macromonomer and the first initiator. The crosslinking agent is a compound or oligomer containing at least two double bonds, and the number average molecular weight of the oligomer is 200 to 5000.

[0030] In one embodiment, the crosslinking agent satisfies any one or two of the following conditions:

[0031] (1) The crosslinking agent is selected from any one or two of trimethylolpropane trimethacrylate, tetra-arm polyethylene glycol acrylate, polyethylene glycol diacrylate, ethylene glycol diallyl ether, pentaerythritol triallyl ether, trimethylolpropane diallyl ether, butanediol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether; and

[0032] (2) The mass of the crosslinking agent is 0.05% to 10% of the total mass of the biodegradable polyester and the macromolecular monomer.

[0033] In one embodiment, the macromonomer is prepared by the following steps:

[0034] Under the conditions of a catalyst and a second initiator, the monomers of the multi-arm biodegradable polyester prepolymer are subjected to ring-opening polymerization to prepare the multi-arm biodegradable polyester prepolymer, wherein the second initiator is a polyhydroxy compound.

[0035] The macromonomer is prepared by reacting the multi-arm biodegradable polyester prepolymer with a substance containing carbon-carbon double bonds and a group capable of reacting with hydroxyl groups, wherein the group capable of reacting with hydroxyl groups is selected from any one or more of acid anhydrides, acyl chlorides, isocyanates and epoxy groups.

[0036] In one embodiment, the preparation steps of the macromonomer satisfy one or more of the following conditions:

[0037] (1) The second initiator accounts for 0.05% to 10% of the molar percentage of the constituent monomers of the multi-arm biodegradable polyester prepolymer;

[0038] (2) The number of hydroxyl groups in the second initiator is 2 to 6;

[0039] (3) The polymerization reaction time is 12h to 96h; and

[0040] (4) The substance containing carbon-carbon double bonds and groups capable of reacting with hydroxyl groups is selected from any one or more of methacrylic anhydride, methacryloyl chloride, isocyanate ethyl methacrylate, glycidyl methacrylate, ethyl isocyanate acrylate, acrylic anhydride, acryloyl chloride, propylene oxide acrylate and allyl glycidyl ether.

[0041] The application of a biodegradable material in the preparation of biodegradable stents, cardiac occluders, surgical sutures, drug-release coatings, tissue filling materials, bone repair products, or food packaging materials, wherein the biodegradable material is the aforementioned biodegradable material or a biodegradable material prepared by the aforementioned method for preparing biodegradable materials.

[0042] A biodegradable scaffold, wherein the material of the biodegradable scaffold includes the above-mentioned biodegradable material or a biodegradable material prepared by the above-mentioned method for preparing biodegradable materials.

[0043] The raw materials for preparing the aforementioned biodegradable materials include high-molecular-weight biodegradable polyesters and low-molecular-weight macromonomers. The acidic products generated by the degradation of the relatively fast-degrading macromonomers can be designed to catalyze the in-situ degradation of the slower-degrading biodegradable polyester. Simultaneously, the overall crystallinity of the material can be controlled by adjusting the amount of macromonomers added, making the degradation cycle of the biodegradable polyester material controllable. Furthermore, the biodegradable polyester and macromonomers form a chemically cross-linked network with a certain content and a spherulitic physical network with a certain degree of crystallinity. This allows the biodegradable material to have a controllable degradation cycle while maintaining good structural stability and not reducing mechanical properties, or even improving them. It can be used in fields such as vascular stents, cardiac occluders, surgical sutures, tissue packing materials, bone repair products, and food packaging. Attached Figure Description

[0044] Figure 1 The image shows the microstructure of the biodegradable material prepared in Example 1 under a polarizing microscope.

[0045] Figure 2 This is an image showing the appearance of the coronary stent prepared in Example 19. Detailed Implementation

[0046] To facilitate understanding of the present invention, a more comprehensive description of the invention will be provided below in conjunction with specific embodiments. Preferred embodiments of the invention are given in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0048] In this article, "multiple XX" means ≥2, for example, multiple arms means two arms or more than two arms.

[0049] In this document, "one or several" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.

[0050] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0051] In this document, the terms “comprising” and “having”, and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that comprises a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or components inherent to such process, method, product, or apparatus.

[0052] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0053] To shorten the degradation cycle of polylactic acid (PLA), traditional techniques use high-molecular-weight PLA, low-molecular-weight PLA, and high-molecular-weight racemic PLA as raw materials to form composite materials. Adding low-molecular-weight PLA and racemic PLA to the system can disrupt the crystallinity of the material and accelerate its degradation rate. However, this method also reduces the mechanical strength of the material, and oligomers are more conducive to relaxation behavior, which reduces mechanical stability and shelf life.

[0054] To improve the mechanical properties of biodegradable polyester materials, existing technologies disclose a polyester composite material made from biodegradable polyester and a metal matrix. While introducing the metal matrix enhances the material's mechanical properties, it significantly impacts the material's two-phase compatibility and processability, ultimately affecting the stability and reliability of the scaffold product. Other technologies utilize ceramic materials as reinforcing agents added to biodegradable materials to improve the mechanical properties of biodegradable scaffolds. However, the degradation mechanism and biosafety of ceramic materials in the human body are unclear, and they also affect the material's toughness, two-phase compatibility, and processability. Still other technologies incorporate homopolymers and inorganic salts as nucleating agents into biodegradable copolymers to improve the mechanical properties of biodegradable polyester scaffolds. This method severely impacts the material's toughness, composite uniformity, and structural stability.

[0055] Therefore, while traditional technologies can improve a specific property of polyester biodegradable materials through various technical means, this usually comes at the cost of a significant decline in other properties, making it difficult to improve and enhance multiple properties simultaneously.

[0056] Based on this, the present invention provides a biodegradable material with a controllable degradation cycle, excellent structural stability, and without reducing or even improving mechanical properties.

[0057] One embodiment of the biodegradable material includes a chemical cross-linked network and a spherulite physical network, wherein the content of the chemical cross-linked network of the biodegradable material is 20% to 100%, and the crystallinity is 5% to 50%.

[0058] The raw materials for preparing biodegradable materials include: biodegradable polyester and macromonomers, including multi-arm biodegradable polyester prepolymers with end-group modified carbon-carbon double bonds;

[0059] Chemical cross-linking networks include chemical cross-linking networks formed by cross-linking of macromolecular monomers, chemical cross-linking networks formed by covalent bonding between macromolecular monomers and biodegradable polyesters, and chemical cross-linking networks formed by covalent bonding between biodegradable polyesters.

[0060] The spherulite physical network includes the spherulite network formed by the degradation of biodegradable polyester.

[0061] Specifically, in some embodiments, macromonomers crosslink through carbon-carbon double bonds at their end groups to form a chemically crosslinked network structure. Biodegradable polyesters form chemically crosslinked networks through hydrogen abstraction or chain transfer. Macromonomers crosslink through carbon-carbon double bonds at their end groups and then transfer to the biodegradable polyester chain to form a chemically crosslinked network. Taking photo-initiated crosslinking as an example, the formation process of the chemically crosslinked network is as follows: After being irradiated with light of a matched wavelength, the photosensitive groups of the photoinitiator (whether hydrogen abstraction type or cleavage type photoinitiator) are excited. Hydrogen abstraction type photoinitiators abstract hydrogen atoms from the "hydrogen donor" to form free radicals, while cleavage type photoinitiators directly cleave to generate free radicals. These free radicals preferentially attack carbon-carbon double bonds (lower energy barrier, more reactive), causing the macromonomers to undergo free radical polymerization through the carbon-carbon double bonds at their end groups to form a chemically crosslinked network. However, not all free radicals generated by photoinitiators attack carbon-carbon double bonds. Some, instead of reaching these bonds, attack the biodegradable polyester chain, forming covalent bonds. Alternatively, the free radical may transfer to the biodegradable polyester chain, forming covalent bonds. Complex connections result in a chemical cross-linking network, formed through chemical bonds between the macromonomer and the biodegradable polyester. Furthermore, if the initial free radical directly attacks the biodegradable polyester, it may remove hydrogen atoms from the chain, creating a new free radical at that location. This radical can then further attack another biodegradable polyester chain, forming a chemical cross-linking network through hydrogen removal between the biodegradable polyesters. The principles behind other initiation methods are the same and will not be elaborated further.

[0062] In a specific example, the content of the chemical cross-linked network of the biodegradable material is 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, or any combination of these values. Optionally, the content of the chemical cross-linked network of the biodegradable material is 20%–90%, 20%–80%, 20%–70%, 20%–60%, 30%–90%, 30%–80%, 30%–70%, 30%–60%, 40%–90%, 40%–80%, 40%–70%, 40%–60%, 50%–90%, 50%–80%, 50%–70%, or 50%–60%. Furthermore, the chemical cross-linking network content of biodegradable materials is 40%–90%. Even further, the chemical cross-linking network content of biodegradable materials is 50%–90%. Even further still, the chemical cross-linking network content of biodegradable materials is 50%–80%. The chemical cross-linking network content reflects the proportion of the chemical cross-linking network.

[0063] By adjusting the number-average molecular weight, number of arms, and content ratio of macromonomers in biodegradable materials, the content of chemical cross-linking networks can be adjusted between 20% and 100%.

[0064] Furthermore, in the raw materials used for preparation, the mass percentage of the macromonomer is 1% to 70%, the number of arms is 2 to 12, and the number-average molecular weight of each arm is 100 to 50,000. The complete degradation cycle of the polyester chain in the macromonomer is 1 month to 2 years.

[0065] In a specific example, the mass percentage of the macromonomer in the raw materials is 1%, 5%, 10%, 12%, 15%, 20%, 22%, 25%, 28%, 30%, 40%, 50%, 60%, 70%, or any combination of these values. Further, the mass percentage of the macromonomer is 5%–30%. Optionally, the mass percentage of the macromonomer is 5%–25%, 5%–20%, 5%–15%, 10%–30%, 10%–25%, 10%–20%, 15%–30%, 15%–25%, or 15%–20%.

[0066] In a specific example, the number of arms of the macromonomer is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 arms, or any combination of these values. Further, the number of arms of the macromonomer is 2 to 6 arms. Even further, the number of arms of the macromonomer is 4 to 6 arms.

[0067] In a specific example, the number-average molecular weight of the macromonomer's single arms is 100, 500, 1000, 2000, 5000, 6000, 8000, 10000, 12000, 15000, 18000, 20000, or any combination of these values. Further, the number-average molecular weight of the macromonomer's single arms is 5000–20000.

[0068] The inventors discovered in their experiments that a higher content of macromonomers and a smaller number-average molecular weight per arm result in a higher crosslinking density after blending with biodegradable polyester. This improves the structural stability and mechanical strength of the biodegradable material, but a higher crosslinking density also prolongs the degradation cycle. At a constant crosslinking density, the faster the macromonomers degrade, the faster the degradation rate after blending with biodegradable polyester. A higher proportion of fast-degrading macromonomers in the blend results in more pronounced in-situ catalytic degradation and a faster degradation rate. Therefore, by comprehensively adjusting the composition and ratio of macromonomers, the performance of biodegradable materials can be effectively controlled.

[0069] The inventors also discovered in their experiments that the overall crystallinity of biodegradable materials has a significant impact on the degradation rate. When the selected macromonomers are non-crystalline and the content of macromonomers is higher, the overall crystallinity of the biodegradable material is lower. The structural stability and mechanical strength of the biodegradable material will decrease to varying degrees, and the reduction in crystallinity will also shorten the overall degradation cycle of the biodegradable material.

[0070] In some embodiments, the content of the chemical cross-linked network of the biodegradable material is 50% to 90%. Further, in the raw materials used for preparation, the macromolecular monomer has a mass percentage of 5% to 30%, has 2 to 6 arms, and a number-average molecular weight of 5000 to 20000 per arm.

[0071] In some embodiments, the multi-arm biodegradable polyester prepolymer is selected from one or more of poly-L-lactide, poly-D-lactide, polyglycolic acid, and poly(ε-caprolactone), or the multi-arm biodegradable polyester prepolymer is selected from copolymers formed by copolymerizing at least two monomers selected from D,L-lactide, D-lactide, L-lactide, glycolide, ε-caprolactone, δ-valerolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, butylene succinate, p-dioxanone, and trimethylene carbonate. In one embodiment, the multi-arm biodegradable polyester prepolymer is a copolymer formed by copolymerizing mixed-rotation lactide (D,L-LA) and caprolactone. For example, the multi-arm biodegradable polyester prepolymer is a copolymer formed by copolymerizing mixed-rotation lactide (D,L-LA) and caprolactone in a molar ratio of 95:5.

[0072] In some embodiments, the spherulitic physical network is formed by the crystallization of biodegradable polyester during a cooling process. Further, the spherulitic physical network is formed by the crystallization of biodegradable polyester from a crystallization temperature (T). c Cooling from the melting temperature to the glass transition temperature (T) g It is formed by crystallization in the following process.

[0073] In one embodiment, the spherulite physical network is formed by crystallization of the biodegradable polyester during the cooling process from 120°C to 200°C to below 50°C, at a cooling rate of 1°C / min to 50°C / min.

[0074] In a specific example, the crystallinity of the biodegradable material is 5%, 10%, 15%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, or a range of any two of these values. Further, the crystallinity of the biodegradable material is 10%–50%. Even further, the crystallinity of the biodegradable material is 20%–50%. Optionally, the crystallinity of the biodegradable material is 20%–45%, 20%–40%, 25%–50%, 25%–45%, 25%–40%, 30%–50%, 30%–45%, or 30%–40%.

[0075] Furthermore, by adjusting the crystallinity of the biodegradable material to 5%–50% and the content of the chemical cross-linking network to 20%–100%, the degradation cycle of the biodegradable material can be adjusted between 1 month and 5 years, the tensile strength between 20 MPa and 200 MPa, and the elongation at break between 3% and 200%.

[0076] By adjusting the molecular weight and content percentage of the biodegradable polyester, the crystallinity can be adjusted between 5% and 50%. Further, in the raw materials, the mass percentage of the biodegradable polyester is 30% to 99%. For example, the mass percentage of the biodegradable polyester can be, but is not limited to, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 72%, 75%, 80%, 82%, 85%, 90%, 92%, 95%, or any combination of these values. Further, the mass percentage of the biodegradable polyester is 70% to 95%. Optionally, the mass percentage of the biodegradable polyester is 70% to 90%, 70% to 85%, 75% to 95%, 75% to 90%, 80% to 95%, 80% to 90%, 85% to 95%, or 85% to 90%.

[0077] Furthermore, the number-average molecular weight of the biodegradable polyester is between 100,000 and 1,000,000. For example, the number-average molecular weight of the biodegradable polyester is 100,000, 150,000, 200,000, 250,000, 300,000, 350,000, 400,000, 450,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000, or any combination of these values. Further, the number-average molecular weight of the biodegradable polyester is between 200,000 and 500,000.

[0078] In some embodiments, the biodegradable polyester has a mass percentage of 70% to 95%, a number average molecular weight of 200,000 to 500,000, and a crystallinity of 20% to 50% for the biodegradable material.

[0079] In some embodiments, the biodegradable polyester is selected from one or more of poly(L-lactide), poly(D-lactide), polyglycolic acid, and poly(ε-caprolactone); or, the biodegradable polyester is selected from copolymers formed by copolymerizing at least two monomers selected from D,L-lactide, D-lactide, L-lactide, glycolide, ε-caprolactone, δ-valerolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, butylene succinate, p-dioxanone, and trimethylene carbonate. Further, the complete degradation period of the biodegradable polyester is 3 months to 5 years. In a specific example, the biodegradable polyester is poly(L-lactide).

[0080] In some embodiments, by adjusting the crystallinity and the content of chemical cross-linking networks of the biodegradable material, the degradation cycle of the biodegradable material can be adjusted between 6 months and 3 years, the tensile strength is between 50 MPa and 180 MPa, and the elongation at break is between 3% and 50%.

[0081] Furthermore, the crystallinity of the biodegradable material is 20%–50%. Correspondingly, the number-average molecular weight of the biodegradable polyester with this crystallinity is 200,000–500,000, and its mass percentage is 70%–95%.

[0082] Furthermore, the content of chemical cross-linked networks in the biodegradable material is 50%–90%. Corresponding to this content of chemical cross-linked networks, the number-average molecular weight of the macromonomers with single arms is 5000–20000, the number of arms is 2–6, and the mass percentage is 5%–30%.

[0083] The aforementioned biodegradable materials have at least the following advantages:

[0084] (1) The raw materials for preparing the above-mentioned biodegradable materials include high molecular weight biodegradable polyester and low molecular weight macromonomers. The acidic products generated by the degradation of macromonomers with fast degradation rates can catalyze the in-situ degradation of slow-degradable polyester materials, making the degradation cycle of biodegradable polyester materials controllable. In addition, biodegradable polyester and macromonomers form a chemical cross-linked network with a certain content and a spherulite physical network with a certain degree of crystallinity, so that the biodegradable materials have good structural stability while having a controllable degradation cycle, and do not reduce mechanical properties or even improve mechanical properties. They can be used in vascular stents, cardiac occluders, surgical sutures, tissue filling materials, bone repair products and food packaging, etc.

[0085] (2) The macromolecular monomers used in the above biodegradable materials have low molecular weights, resulting in low melt viscosity. They can be used as plasticizers to reduce the melt viscosity of the blended system, thereby reducing the molding and processing temperature of the material and weakening the degradation of the material during processing.

[0086] One embodiment of the method for preparing a biodegradable material includes the following steps:

[0087] Biodegradable polyester, macromonomer and first initiator are mixed and then crosslinked. The mixture is then cooled at a rate of 1℃ / min to 50℃ / min to below the glass transition temperature of the biodegradable polyester to prepare a biodegradable material. The temperature of the crosslinking reaction is between the crystallization temperature and the melting temperature of the biodegradable polyester.

[0088] Among them, the number average molecular weight of biodegradable polyester is ≥100,000, and the macromonomers include multi-arm biodegradable polyester prepolymers with end-group modified carbon-carbon double bonds.

[0089] In some embodiments, based on the total mass of the biodegradable polyester and macromonomers as 100%, the mass percentage of the biodegradable polyester is 30% to 99%, and the mass percentage of the macromonomers is 1% to 70%. Further, the mass percentage of the biodegradable polyester is 70% to 95%, and the mass percentage of the macromonomers is 5% to 30%.

[0090] In some embodiments, the biodegradable polyester, macromonomer and first initiator are mixed by melt blending.

[0091] In some embodiments, the crosslinking reaction temperature is 120°C to 200°C. For example, the crosslinking reaction temperature is 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or any combination of these values. Further, the crosslinking reaction temperature is 120°C to 150°C. By conducting the crosslinking reaction above the crystallization temperature of the biodegradable polyester, the segments of the biodegradable polyester and macromonomers can move sufficiently to undergo crosslinking, thereby increasing the content of the chemical crosslinking network.

[0092] In some embodiments, the crosslinking reaction time is 1 min to 30 min. For example, the crosslinking reaction time is 1 min, 2 min, 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min, 28 min, 30 min, or any range of two of these values. Further, the crosslinking reaction time is 5 min to 20 min.

[0093] In some embodiments, the first initiator is a photoinitiator, and the crosslinking reaction step includes: irradiating with ultraviolet light at 120°C to 200°C for 1 min to 30 min.

[0094] In other embodiments, the first initiator is a thermal initiator, and the crosslinking reaction step includes: carrying out the crosslinking reaction at 120°C to 200°C for 1 min to 30 min.

[0095] In other embodiments, the crosslinking reaction includes initiating the crosslinking reaction by irradiation with high-energy rays at 120°C to 200°C for 1 min to 30 min. For example, the crosslinking reaction is initiated by irradiation with gamma rays, electron beams, or X-rays. Further, the crosslinking reaction lasts for 5 min to 30 min. It is understood that high-energy ray irradiation-initiated crosslinking enables the carbon-carbon double bonds to crosslink without the need for an additional initiator. However, in some embodiments, an initiator may be added, and the crosslinking effect is better with an initiator.

[0096] In some embodiments, the thermal initiator is selected from one or more of azo initiators and peroxide initiators. For example, thermal initiators include, but are not limited to, benzoyl peroxide, azobisisobutyl cyanide, and di-tert-butyl peroxide. The photoinitiator is selected from cleavage-type photoinitiators and hydrogen-abstraction-type photoinitiators. For example, photoinitiators include, but are not limited to, benzoin and its derivatives, benzoyl groups, alkyl phenyl ketones, acyl phosphorus oxides, benzophenones, and thioxanthone photoinitiators.

[0097] Taking photoinitiators as an example, the crosslinking reaction process is as follows: After being irradiated with light of a matched wavelength, the photosensitive groups of the photoinitiator (whether hydrogen-abstracting or cleavage-type) are excited. Hydrogen-abstracting photoinitiators will abstract hydrogen atoms from the "hydrogen donor" to form free radicals, while cleavage-type photoinitiators will directly cleave to generate free radicals. The generated free radicals preferentially attack carbon-carbon double bonds (low energy barrier), causing the macromonomer to undergo free radical polymerization through the carbon-carbon double bonds of the terminal groups to form a chemical crosslinking network. However, not all free radicals generated by photoinitiators attack carbon-carbon double bonds. Some, unable to reach the carbon-carbon double bonds, will attack the biodegradable polyester chain, thus forming covalent bonds. Alternatively, free radicals may transfer carbon to the biodegradable polyester, forming covalent bonds. Complex connections result in a chemical crosslinking network, which is formed through chemical bonds between the macromonomer and the biodegradable polyester. Furthermore, if the initial free radical directly attacks the biodegradable polyester, it can capture hydrogen atoms from the biodegradable polyester chain, forming a free radical at that site. This free radical can then further attack another biodegradable polyester chain, thus forming a "chemical cross-linking network between biodegradable polyesters through hydrogen capture." The principles of other initiation methods are the same and will not be elaborated further.

[0098] Further, the amount of the first initiator added is 0.05% to 5% of the total mass of the biodegradable polyester and macromonomer. For example, the amount of the first initiator added is 0.05%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5% or any range of two of these values, based on the total mass of the biodegradable polyester and macromonomer. Further, the amount of the first initiator added is 0.5% to 2% of the total mass of the biodegradable polyester and macromonomer.

[0099] In some embodiments, the crosslinking reaction temperature is 120°C to 200°C. The step of carrying out the crosslinking reaction and then cooling at a rate of 1°C / min to 50°C / min to below the glass transition temperature of the biodegradable polyester includes: carrying out the crosslinking reaction at 120°C to 200°C and then cooling at a rate of 1°C / min to 50°C / min to below 50°C.

[0100] For example, the cooling rate can be 1℃ / min, 2℃ / min, 5℃ / min, 8℃ / min, 10℃ / min, 12℃ / min, 15℃ / min, 18℃ / min, 20℃ / min, 22℃ / min, 25℃ / min, 28℃ / min, 30℃ / min, 40℃ / min, 50℃ / min, or any combination of these values. Further, the cooling rate can be between 5℃ / min and 20℃ / min. Excessively rapid cooling results in lower crystallinity, reduced mechanical strength, accelerated degradation, and decreased aging stability of the material.

[0101] In some embodiments, a crosslinking agent is also added in the step of mixing the biodegradable polyester, the macromonomer and the first initiator. The crosslinking agent is a compound or oligomer containing at least two double bonds, and the number average molecular weight of the oligomer is 200 to 5000.

[0102] Furthermore, the crosslinking agent is selected from any one or two of trimethylolpropane trimethacrylate, tetra-arm polyethylene glycol acrylate, polyethylene glycol diacrylate, ethylene glycol diallyl ether, pentaerythritol triallyl ether, trimethylolpropane diallyl ether, butanediol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether.

[0103] Further, the mass of the crosslinking agent is 0.05% to 10% of the total mass of the biodegradable polyester and macromonomers. For example, the mass of the crosslinking agent is 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any combination of these values, based on the total mass of the biodegradable polyester and macromonomers. Further, the mass of the crosslinking agent is 0.5% to 2% of the total mass of the biodegradable polyester and macromonomers.

[0104] Adding small-molecule crosslinking agents can significantly increase the content of chemical crosslinking networks and improve aging stability.

[0105] In some embodiments, a polymerization inhibitor is also added during the step of mixing the biodegradable polyester, the macromonomer, and the first initiator. The polymerization inhibitor can prevent or delay the polymerization reaction, protect the double bond activity, and prevent the double bonds of the macromonomer from being opened and deactivated during post-processing and storage. Further, the polymerization inhibitor includes, but is not limited to, any one or more of p-tert-butylcatechol, 4-methoxyphenol, hydroquinone, 1,4-naphthoquinone, and p-phenylenediamine.

[0106] In one embodiment, the mass of the polymerization inhibitor is 0.01% to 1% of the total mass of the biodegradable polyester and macromonomer.

[0107] In some embodiments, the preparation steps of the macromonomer include:

[0108] Under the conditions of a catalyst and a second initiator, the monomers of the multi-arm biodegradable polyester prepolymer are subjected to ring-opening polymerization to prepare the multi-arm biodegradable polyester prepolymer. The second initiator is a polyhydroxy compound.

[0109] A multi-arm biodegradable polyester prepolymer is reacted with a substance containing carbon-carbon double bonds and a group capable of reacting with hydroxyl groups. The group capable of reacting with hydroxyl groups is selected from any one or more of acid anhydrides, acyl chlorides, isocyanates, and epoxy groups to prepare a macromonomer.

[0110] In one embodiment, the monomer of the multi-arm biodegradable polyester prepolymer is selected from any one or more of D,L-lactide, L-lactide, D-lactide, glycolide, ε-caprolactone, δ-valerolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, butylene succinate, p-dioxanone, and trimethylene carbonate.

[0111] In one embodiment, the second initiator comprises 0.05% to 10% of the constituent monomers of the multi-arm biodegradable polyester prepolymer in molar percentage. For example, the second initiator comprises 0.05%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 10%, or any combination of these values. Further, the second initiator comprises 0.1% to 1% of the constituent monomers of the multi-arm biodegradable polyester prepolymer in molar percentage.

[0112] In one embodiment, the polymerization reaction time is 12h to 96h. For example, the polymerization reaction time is 12h, 24h, 36h, 48h, 60h, 72h, 84h, 96h, or any range of two of these values. Further, the polymerization reaction time is 12h to 48h.

[0113] The number-average molecular weight of the single arms of the obtained multi-arm biodegradable polyester prepolymer can be adjusted by changing the amount of the second initiator and the polymerization reaction time. In one embodiment, the number-average molecular weight of the single arms of the biodegradable polyester prepolymer is 100–20,000. Further, the number-average molecular weight of the single arms of the biodegradable polyester prepolymer is 5,000–20,000.

[0114] In some embodiments, the polyhydroxy compound is selected from ethylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,10-decanediol, n-decanediol, tripropylene glycol, triethylene glycol, triethylene glycol dimethacrylate, triethylene glycol dimethyl ether, dipropylene glycol methyl ether, triethylene glycol mono-11-mercaptoundecyl ether, 2-phenyl-1,3-propanediol, triethylene glycol monobutyl ether, triethylene glycol methyl ether methacrylate, and compounds with a number average molecular weight of 200-200. The following are some of the following: polyethylene glycol (PEG) with a number average molecular weight of 0000; poly(tetrahydrofuran) glycol with a number average molecular weight of 200 to 20000; polycaprolactone triol; trihydroxypolyoxypropylene ether; 1,2,3-heptanetriol; 1,2,6-hexanetriol; trimethylolpropane; tri(hydroxymethyl)aminomethane; 3-methyl-1,3,5-pentanetriol; 1,2,7,8-octanetriol; pentaerythritol propoxylated; pentaerythritol; and dipentaerythritol.

[0115] The number of arms in the prepared biodegradable polyester prepolymer is adjusted by changing the number of hydroxyl groups contained in the second initiator. In one embodiment, the number of arms in the biodegradable polyester prepolymer is 2 to 12 arms. Further, the number of arms in the biodegradable polyester prepolymer is 2 to 6 arms.

[0116] In some embodiments, the catalyst is selected from one or more of stannous octoate, aluminum isopropoxide, diethylzinc, and stannous trifluoromethanesulfonate.

[0117] In some embodiments, the substance containing a carbon-carbon double bond and a group capable of reacting with a hydroxyl group is selected from any one or more of methacrylic anhydride, methacryloyl chloride, isocyanate ethyl methacrylate, glycidyl methacrylate, ethyl isocyanate acrylate, acrylic anhydride, acryloyl chloride, propylene oxide acrylate, and allyl glycidyl ether.

[0118] In some embodiments, the molar ratio of the substance containing carbon-carbon double bonds and groups capable of reacting with hydroxyl groups to the biodegradable polyester prepolymer is (n~1.5n):1. Wherein, n is the number of arms of the multi-arm biodegradable polyester prepolymer.

[0119] In some embodiments, the reaction time between the multi-arm biodegradable polyester prepolymer and a substance containing carbon-carbon double bonds and groups capable of reacting with hydroxyl groups is 5 min to 2 h, further, the reaction time is 5 min to 1 h, and more preferably, the reaction time is 10 min to 0.5 h. The reaction temperature is 80 °C to 150 °C.

[0120] In some embodiments, the structural formula of the macromonomer is as follows:

[0121]

[0122] Wherein, B is the repeating unit of the multi-arm biodegradable polyester prepolymer; m is the number of repeating units; I' is the terminal residue of the initiator; and p is the number of arms of the macromonomer (p≥2). Expresses the linking portion between carbon-carbon double bonds and multi-arm biodegradable polyester prepolymers; It represents a carbon-carbon double bond;

[0123] The above-mentioned method for preparing biodegradable materials is simple, and by controlling parameters such as the temperature and cooling rate of the cross-linking reaction, the crystallinity and chemical cross-linking network content of the prepared biodegradable materials can be adjusted to suitable values. This allows the biodegradable materials to have a controllable degradation cycle, good aging stability, and to maintain or even improve mechanical properties.

[0124] The above-mentioned biodegradable materials are used in the preparation of biodegradable stents, cardiac occluders, surgical sutures, drug-release coatings, tissue filling materials, bone repair products, or food packaging materials.

[0125] In some embodiments, the biodegradable material can also be blended with functional materials during the preparation process to prepare functional composite materials for use in medical devices and food packaging.

[0126] Optionally, functional materials include, but are not limited to, imaging materials, natural polymer materials, antibacterial materials, anticoagulant materials, and endothelialization-promoting materials.

[0127] The aforementioned biodegradable materials possess excellent structural stability and mechanical properties, and have a controllable degradation cycle. They can be widely used in fields such as biodegradable stents, cardiac occluders, surgical sutures, drug-releasing coatings, tissue filling materials, bone repair, and food packaging.

[0128] One embodiment of the biodegradable scaffold includes materials comprising the aforementioned biodegradable materials.

[0129] In one embodiment, a biodegradable scaffold is prepared by processing steps such as blending raw materials of biodegradable materials, tubing extrusion, blow molding, crosslinking, cooling crystallization, and laser cutting.

[0130] In one embodiment, the degradation cycle of the biodegradable stent can be controllably adjusted between 1 and 3 years, and the radial support force can be adjusted between 100 kPa and 200 kPa.

[0131] To make the objectives and advantages of the present invention clearer, the biodegradable materials and their effects of the present invention are further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and should not be used to limit the present invention. Unless otherwise specified, the following embodiments do not include components other than unavoidable impurities. Unless otherwise specified, the drugs and instruments used in the embodiments are conventional choices in the art. Experimental methods in the embodiments that do not specify specific conditions are implemented according to conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.

[0132] Example 1

[0133] This embodiment provides a biodegradable material, the preparation process of which is as follows:

[0134] (1) Synthesis of macromonomers: 191.32 g of mixed-rotation lactide (D,L-LA), 7.98 g of caprolactone (CL) monomer, 0.70 g of dipentaerythritol and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at 140 °C. Then, after continuous vacuum for 1 h, 0.06 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 3.0 g of isocyanate methacrylate and further reaction for 0.5 h, finally yielding a six-armed macromonomer DPE-PLC 95 with a terminal carbon-carbon double bond structure (theoretical molar ratio of D,L-LA to CL is 95:5, theoretical number-average molecular weight of single arm is 12000).

[0135] (2) Preparation of biodegradable material: Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared above. 0.5% of the total mass of polylactic acid and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then lowered to 130°C at a rate of 30°C / min and irradiated with a 365nm UV lamp for 10 min. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0136] The theoretical single-arm molecular weight is obtained as follows: Assuming the desired total molecular weight is 72,000 (6 arms, with each arm being 12,000), and the theoretical molar ratio of D,L-LA to CL is 95:5, the amount of D,L-LA and CL to be added can be calculated. Conversely, the amount of D,L-LA and CL to be added will yield a macromonomer with a single-arm molecular weight of 12,000.

[0137] Example 2

[0138] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the ratio of biodegradable polyester to macromolecular monomer in step (2) is different. Step (2) of this embodiment is as follows:

[0139] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and the six-armed macromonomer DPE-PLC 95 was dissolved in dichloromethane at a ratio of 70:30 (w / w). 0.5% of the total mass of PLLA and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until completely dissolved, and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes. The temperature was then lowered to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 minutes. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0140] Example 3

[0141] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the ratio of biodegradable polyester to macromolecular monomer in step (2) is different. Step (2) of this embodiment is as follows:

[0142] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and the six-armed macromonomer DPE-PLC 95 was dissolved in dichloromethane in a ratio of 50:50 (w / w). 0.5% of the total mass of PLLA and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until completely dissolved, and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes. The temperature was then lowered to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 minutes. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0143] Example 4

[0144] This embodiment provides a biodegradable material, which differs from Example 1 in that the number of arms of the macromolecular monomer is different. The preparation process of the biodegradable material in this embodiment is as follows:

[0145] (1) 95.7 g of mixed-rotation lactide (D,L-LA), 3.98 g of caprolactone (CL) monomer, 0.375 g of 1,4-butanediol and 34.2 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at a temperature of 140 °C. Then, after continuous vacuum for 1 h, 0.03 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 1.5 g of isocyanate methacrylate and further reaction for 0.5 h, finally yielding a two-armed macromonomer BDO-PLC 95 with a terminal carbon-carbon double bond structure (theoretical molar ratio of D,L-LA to CL is 95:5, theoretical number-average molecular weight of single arm is 12000).

[0146] (2) Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the two-arm macromonomer BDO-PLC95 prepared above. 0.5% of the total mass of polylactic acid and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then reduced to 130°C at a rate of 30°C / min and irradiated with a 365nm UV lamp for 10 min. Finally, the temperature was reduced to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0147] Example 5

[0148] This embodiment provides a biodegradable material, which differs from Example 1 in that the number of arms of the macromolecular monomer is different. The preparation process of the biodegradable material in this embodiment is as follows:

[0149] (1) Synthesis of macromonomers: 95.7 g of mixed-phase lactide (D,L-LA), 3.98 g of caprolactone (CL) monomer, 0.373 g of trimethylolpropane (TMP), and 34.2 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at 140 °C. Then, after continuous vacuum for 1 h, 0.03 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 1.5 g of isocyanate methacrylate and further reaction for 0.5 h. Finally, a three-arm macromonomer TMP-PLC 95 with a terminal carbon-carbon double bond structure was obtained (the theoretical molar ratio of D,L-LA to CL is 95:5, and the theoretical number-average molecular weight of the single arm is 12000).

[0150] (2) Preparation of biodegradable material: Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the three-arm macromonomer TMP-PLC95 prepared above. 0.5% of the total mass of polylactic acid and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then reduced to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 min. Finally, the temperature was reduced to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0151] Example 6

[0152] This embodiment provides a biodegradable material, which differs from Example 1 in that the number-average molecular weight of the single arm of the macromolecular monomer is different. The preparation process of the biodegradable material in this embodiment is as follows:

[0153] (1) Synthesis of macromonomers: 190.66 g of mixed-rotation lactide (D,L-LA), 7.94 g of caprolactone (CL) monomer, 1.40 g of dipentaerythritol, and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at 140 °C. Then, after continuous vacuum for 1 h, 0.06 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 6.0 g of isocyanate methacrylate and further reaction for 0.5 h. Finally, a six-arm macromonomer DPE-PLC 95 with a terminal carbon-carbon double bond structure was obtained (D,L-LA to CL molar ratio of 95:5), with a theoretical number-average molecular weight of 6000 for each arm.

[0154] (2) Preparation of biodegradable material: Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared above. 0.5% of the total mass of polylactic acid and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then reduced to 130°C at a rate of 30°C / min and irradiated with a 365nm UV lamp for 10 min at this temperature. Finally, the temperature was reduced to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0155] Example 7

[0156] This embodiment provides a biodegradable material, which differs from Example 1 in that the number-average molecular weight of the single arm of the macromolecular monomer is different. The preparation process of the biodegradable material in this embodiment is as follows:

[0157] (1) Synthesis of macromonomers: 189.31 g of mixed-rotation lactide (D,L-LA), 7.89 g of caprolactone (CL) monomer, 2.8 g of dipentaerythritol and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at 140 °C. Then, after continuous vacuum for 1 h, 0.06 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 12.0 g of isocyanate methacrylate and further reaction for 0.5 h. Finally, a six-arm macromonomer DPE-PLC 95 with a terminal carbon-carbon double bond structure was obtained (D,L-LA to CL molar ratio of 95:5), with a theoretical number-average molecular weight of 3000 for each arm.

[0158] (2) Preparation of biodegradable material: Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared above. 0.5% of the total mass of polylactic acid and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then reduced to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 min. Finally, the temperature was reduced to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0159] Example 8

[0160] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the molecular weight of the biodegradable polyester is different in step (2). Step (2) of this embodiment is specifically as follows:

[0161] Polylactic acid (PLLA) with a number average molecular weight of 200,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared above. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film, and after the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes. The temperature was then lowered to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 minutes. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0162] Example 9

[0163] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the molecular weight of the biodegradable polyester in step (2) is different. Step (2) in this embodiment is specifically as follows:

[0164] Polylactic acid (PLLA) with a number average molecular weight of 100,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared above. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film, and after the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes. The temperature was then lowered to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 minutes. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0165] Example 10

[0166] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the crosslinking temperature in step (2) is different. Step (2) in this embodiment is specifically as follows:

[0167] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 160°C hot plate for molding for 5 minutes, and then irradiated with a 365nm UV lamp at 200°C for 10 minutes. The mixture was then cooled to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0168] Example 11

[0169] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the cooling rate in step (2) is different. Step (2) in this embodiment is specifically as follows:

[0170] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 130°C at a rate of 30°C / min. At this temperature, the material was irradiated with a 365nm UV lamp for 10 minutes and then cooled to room temperature at a rate of 5°C / min. This yielded the biodegradable material of this embodiment.

[0171] Example 12

[0172] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the crosslinking and cooling processes in step (2) are different. Step (2) in this embodiment is specifically as follows:

[0173] Polylactic acid (PLLA) with a number average molecular weight of 100,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 130°C at a rate of 30°C / min. The film was then irradiated with 365nm UV light at 130°C for 10 minutes, and finally cooled to room temperature at a rate of 50°C / min to prepare the biodegradable material of this embodiment.

[0174] Example 13

[0175] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that a small molecule crosslinking agent is added in step (2). Step (2) of this embodiment is specifically as follows:

[0176] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95. 0.5% of the total mass of PLLA and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, and 0.5% of the total mass of PLLA and macromonomer as a small molecule crosslinking agent, trimethylolpropene. The mixture was stirred until completely dissolved, and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes. The temperature was then lowered to 130°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at this temperature for 10 minutes. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0177] Example 14

[0178] This embodiment provides a biodegradable material, which differs from Example 1 in that the composition and ratio of the macromolecular monomers are different. The specific preparation process of the biodegradable material in this embodiment is as follows:

[0179] (1) Synthesis of macromonomers: 191.2 g of mixed-rotation lactide (D,L-LA), 8.1 g of glycolide (GA) monomer, 0.70 g of dipentaerythritol, and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted at 140 °C for 12 h under nitrogen protection. After continuous vacuuming for 1 h, 0.06 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 3.0 g of isocyanate methacrylate and further reaction for 0.5 h, finally yielding a six-armed macromonomer DPE-PLG 95 with a terminal carbon-carbon double bond structure (D,L-LA to GA molar ratio of 95:5, theoretical number-average molecular weight of 12000 for each arm).

[0180] (2) Preparation of biodegradable material: Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane with the six-armed macromonomer DPE-PLG 95 at a ratio of 90:10 (w / w). 0.5% of the total mass of PLLA and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then reduced to 130°C at a rate of 30°C / min and irradiated with a 365nm UV lamp for 10 min. Finally, the temperature was reduced to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0181] Example 15

[0182] This embodiment provides a biodegradable material, which differs from Example 1 in that the composition and ratio of the macromolecular monomers are different. The specific preparation process of the biodegradable material in this embodiment is as follows:

[0183] (1) Synthesis of macromonomers: 182.93 g of mixed-rotation lactide (D,L-LA), 16.36 g of glycolide (GA) monomer, 0.70 g of dipentaerythritol, and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at 140 °C. After continuous vacuuming for 1 h, 0.06 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 3.0 g of isocyanate methacrylate and further reaction for 0.5 h, finally yielding a six-armed macromonomer DPE-PLG 90 with a terminal carbon-carbon double bond structure (D,L-LA to GA molar ratio of 90:10, theoretical number-average molecular weight of 12000 for each arm).

[0184] (2) Preparation of biodegradable material: Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane with the six-armed macromonomer DPE-PLG 90 at a ratio of 90:10 (w / w). 0.5% of the total mass of polylactic acid and macromonomer was added as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min. The temperature was then reduced to 130°C at a rate of 30°C / min and irradiated with a 365nm UV lamp for 10 min. Finally, the temperature was reduced to room temperature at a rate of 10°C / min to prepare the biodegradable material of this embodiment.

[0185] Example 16

[0186] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the photoinitiator used in step (2) is different. Step (2) of this embodiment is specifically as follows:

[0187] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared in Example 1. 0.25% of 4,4'-bis(diethylamino)benzophenone and 0.25% of benzophenone (based on the total mass of PLLA and macromonomer) were added, and the mixture was stirred until completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 130°C at a rate of 30°C / min. At this temperature, the material was irradiated with 365nm ultraviolet light for 10 minutes, and then cooled to room temperature at a rate of 10°C / min to obtain the biodegradable material of this example.

[0188] Example 17

[0189] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that a thermal initiator is used in step (2). The specific preparation process of the biodegradable material in this embodiment is as follows:

[0190] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared in Example 1. Di-tert-butyl peroxide was added at 0.5% of the total mass of PLLA and macromonomer, and the mixture was stirred until completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 130°C at a rate of 30°C / min and held for 10 minutes. Finally, it was cooled to room temperature at a rate of 10°C / min to prepare the biodegradable material of this example.

[0191] Example 18

[0192] This embodiment provides a biodegradable material, which differs from Embodiment 1 in that the initiation method in step (2) is different. Step (2) in this embodiment is specifically as follows:

[0193] Polylactic acid (PLLA) with a number-average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromolecular monomer DPE-PLC 95 prepared in Example 1. The mixture was stirred until the material was completely dissolved and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min, and then cooled to 130°C at a rate of 30°C / min. The material was then transferred to a 130°C hot plate and then transferred as a whole to be irradiated with electron beams at an irradiation dose of 30 kGy for 10 min. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this example.

[0194] Comparative Example 1

[0195] This comparative example provides a biodegradable material, the specific preparation process of which is as follows:

[0196] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected, dissolved in dichloromethane and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent was completely evaporated, the material was placed on a 200°C hot plate for molding for 5 min, then cooled to 130°C at a rate of 30°C / min, and then cooled to room temperature at a rate of 10°C / min to prepare the biodegradable material of Comparative Example 1.

[0197] Comparative Example 2

[0198] This comparative example provides a biodegradable material, which differs from Example 1 in that the crosslinking and cooling processes in step (2) are different. Step (2) of this comparative example is as follows:

[0199] Polylactic acid (PLLA) with a number average molecular weight of 100,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 130°C at a rate of 30°C / min. The film was then irradiated with 365nm UV light at 130°C for 10 minutes, and finally cooled to room temperature at a rate of 100°C / min to prepare the biodegradable material of this comparative proportion.

[0200] Comparative Example 3

[0201] This comparative example provides a biodegradable material, which differs from Example 1 in that the crosslinking and cooling processes in step (2) are different. Step (2) of this comparative example is as follows:

[0202] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared in Example 1. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added. The mixture was stirred until completely dissolved, and then film-coated. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 60°C at a rate of 30°C / min, and irradiated with a 365nm UV lamp at 60°C for 10 minutes. Finally, the temperature was lowered to room temperature at a rate of 10°C / min to prepare the biodegradable material of this comparative example.

[0203] Comparative Example 4

[0204] This comparative example provides a biodegradable material, which differs from Example 1 in that the crosslinking and cooling processes in step (2) are different. Step (2) of this comparative example is as follows:

[0205] Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was selected and dissolved in dichloromethane at a ratio of 90:10 (w / w) with the six-armed macromonomer DPE-PLC 95 prepared in Example 1. 0.5% of the total mass of PLLA and macromonomer as a UV photoinitiator, 4,4'-bis(diethylamino)benzophenone, was added and stirred until the material was completely dissolved. The mixture was then laid into a film. After the solvent had completely evaporated, the material was placed on a 200°C hot plate for molding for 5 minutes, then cooled to 130°C at a rate of 30°C / min, and then to room temperature at a rate of 10°C / min. Finally, the material was irradiated with a 365nm UV lamp at room temperature for 10 minutes to prepare the biodegradable material of this comparative example.

[0206] Comparative Example 5

[0207] This comparative example provides a biodegradable material, which differs from Example 1 in that the synthesis of the macromolecular monomer in step (1) is different. The specific steps (1) of this comparative example are as follows:

[0208] (1) Synthesis of macromonomers: 191.32 g of mixed lactide (D,L-LA), 7.98 g of caprolactone (CL) monomer, 0.70 g of dipentaerythritol and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask. The mixture was reacted for 12 h under nitrogen protection and at a temperature of 140 °C to obtain the six-armed macromolecule DPE-PLC 95 (the theoretical molar ratio of D,L-LA to CL is 95:5, and the theoretical number-average molecular weight of the single arm is 12000).

[0209] Comparative Example 6

[0210] This comparative example provides a biodegradable material, which differs from Example 1 in that the synthesis of the macromolecular monomer in step (1) is different. The specific steps (1) of this comparative example are as follows:

[0211] (1) Synthesis of macromonomers: 189.0 g of mixed-rotation lactide (D,L-LA), 7.87 g of caprolactone (CL) monomer, 3.1 g of dodecyl alcohol and 68.4 mg of stannous octoate (100 ppm) were added to a 500 mL three-necked flask and reacted for 12 h under nitrogen protection and at 140 °C. Then, after continuous vacuum for 1 h, 0.06 g of 4-methoxyphenol was added and stirred for 0.5 h under nitrogen protection, followed by the addition of 3.0 g of isocyanate methacrylate and further reaction for 0.5 h, finally yielding a single-arm macromonomer PLC 95 with a terminal carbon-carbon double bond structure (theoretical molar ratio of D,L-LA to CL is 95:5, theoretical number-average molecular weight of single arm is 12000).

[0212] Example 19

[0213] This embodiment provides a coronary stent, the specific preparation steps of which are as follows:

[0214] (1) Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was dried at 70°C for 12 hours. The six-armed macromonomer DPE-PLC 95 prepared in Example 1 was obtained. The dried PLLA and DPE-PLC 95 were blended at a ratio of 90:10 (w / w), and 0.5% of the total mass of polylactic acid and macromonomer as ultraviolet photoinitiator 4,4'-bis(diethylamino)benzophenone was added and mixed thoroughly.

[0215] (2) Add the mixed material to the feed port of a single screw extruder, set the screw extrusion temperature to 220℃ and the outlet temperature to 180℃, and extrude a pipe with an outer diameter of 1.4mm and a wall thickness of 0.5mm.

[0216] (3) The extruded pipe is blow-molded and the diameter is changed by using a blow molding machine. The blow molding temperature is set to 130℃. After blow molding, the pipe is cross-linked by 365nm ultraviolet light at 130℃ for 10 minutes. The outer diameter of the pipe after blow molding and cross-linking is 3.5mm and the wall thickness is 0.125mm. The temperature is reduced from 130℃ to room temperature at a cooling rate of 10℃ / min to obtain the blow-molded cross-linked pipe.

[0217] (4) The blow-molded cross-linked tube is cut into a coronary stent with a length of 13 mm and a surface coverage of 25% by femtosecond laser (without imaging points and coating).

[0218] Comparative Example 7

[0219] This comparative example provides a coronary stent, the specific fabrication process of which is as follows:

[0220] (1) Polylactic acid (PLLA) with a number average molecular weight of 400,000 and a molecular weight distribution width of 2 was dried in a forced-air dryer at 70°C for 12 hours.

[0221] (2) Add the dried material from step (1) to the feed port of a single screw extruder, set the screw extrusion temperature range to 220°C and the outlet temperature to 180°C, and extrude a pipe with an outer diameter of 1.4 mm and a wall thickness of 0.5 mm.

[0222] (3) The extruded pipe is blow-molded and the diameter is changed by using a blow molding machine. The blow molding temperature is set to 130℃ and the holding time is 10min. After blow molding, the outer diameter of the pipe is 3.5mm and the wall thickness is 0.125mm. The temperature is reduced from 130℃ to room temperature at a cooling rate of 10℃ / min to obtain the blow-molded pipe.

[0223] (4) The blow-molded tube is cut into coronary stents with a length of 13mm and a surface coverage of 25% by femtosecond laser (without imaging points and coating).

[0224] The following is the specific test section:

[0225] 1. Structural characterization

[0226] (1) Microscopic morphology characterization

[0227] The biodegradable material was sliced ​​into a 10 μm thick film and observed under a polarizing microscope (50x magnification) to record its microstructure.

[0228] (2) Crystallinity test

[0229] The thermal changes of biodegradable materials were tested using a DSC (TA Q2000) instrument. A DSC heating program was set, with the temperature increasing from 20℃ to 200℃ at a rate of 10℃ / min. The enthalpy change-temperature curve was obtained, and the enthalpy change ΔH for cold crystallization was calculated by integration. cc and melting enthalpy change ΔH m The formula for calculating crystallinity is as follows:

[0230] Crystallinity (%) = (ΔH) m –△H cc ) / △H0

[0231] (△H0 represents the melt enthalpy change of a 100% crystalline linear high molecular weight biodegradable polyester material)

[0232] (3) Gel content test

[0233] Accurately weigh the initial mass of the biodegradable material sample to be tested, denoted as m0. Add more than 100 times its weight of dichloromethane to the sample, immerse the sample at room temperature for 2 hours, remove the sample, and finally place the sample in a fume hood for free evaporation for 24 hours until the sample reaches constant weight, denoted as m. t The formula for calculating the percentage of chemically cross-linked networks (i.e., gel content) is as follows:

[0234] Percentage of chemically cross-linked networks (gel content) (%) = m t / m0×100%

[0235] 2. Material performance testing:

[0236] (1) Evaluation of mechanical properties:

[0237] The sample was cut into rectangular strips and subjected to a tensile test using a universal tensile testing machine. The tensile rate was set to 10 mm / min and the initial displacement was set to 2.5 cm. The test was stopped when the strip broke. The system automatically calculated / measured the maximum tensile strength and elongation at break.

[0238] (2) Accelerated degradation evaluation of degradation cycle:

[0239] The initial weight of the sample was recorded as m0. The sample was then immersed in phosphate buffer (pH approximately 7.4) and placed in a constant temperature and humidity chamber at 60°C and 60% humidity for accelerated degradation. The sample weight was monitored at different degradation time points and recorded as m0. t The mass loss of samples at different time points is calculated using the following formula: Mass loss ratio = (m0 - m) / ( ... t ) / m0×100%.

[0240] (3) Aging stability evaluation:

[0241] The samples were packaged in nitrogen-filled aluminum foil bags and placed in a constant temperature and humidity chamber at 50℃ and 60% humidity for accelerated aging experiments. The mechanical strength of the samples after 3 months, 6 months and 12 months of aging was tested using a universal tensile testing machine according to the test method in (1). The percentage decrease in tensile strength after 12 months of aging at 50℃ (%) = (initial tensile strength - tensile strength after 12 months of aging at 50℃) / initial tensile strength × 100%.

[0242] Experimental results:

[0243] 1. The microstructure of the biodegradable material prepared in Example 1 under a polarizing microscope is as follows: Figure 1 As shown in the figure, biodegradable materials exhibit a distinct spherulitic physical network.

[0244] 2. The appearance of the coronary stent prepared in Example 19 is as follows: Figure 2 As shown, the stent prepared in Comparative Example 7 has no obvious difference in appearance.

[0245] 3. The performance tests of the biodegradable materials in each embodiment and comparative example are shown below.

[0246] The performance tests of the biodegradable materials in Examples 1-3 and Comparative Example 1 are shown in Table 1 below:

[0247] Table 1

[0248]

[0249]

[0250] As can be seen from the comparison of Examples 1-3 and Comparative Example 1, under the same conditions, as the amount of macromolecular monomer added increases, the crystallinity of the biodegradable material gradually decreases and the gel content increases significantly.

[0251] Compared with Comparative Example 1, the maximum tensile strength of the biodegradable materials prepared in Examples 1-3 did not decrease significantly, and the maximum tensile strength of Examples 1-2 was even higher than that of Comparative Example 1. The elongation at break of the biodegradable materials prepared in Examples 1-3 decreased slightly.

[0252] Compared to Comparative Example 1, the biodegradable materials prepared in Examples 1-3 showed significantly faster mass loss during the accelerated degradation process at 60°C. The mass loss ratios from slowest to fastest were: Comparative Example 1 < Example 1 < Example 2 < Example 3, meaning that the higher the content of the macromolecular monomer, the faster the degradation rate.

[0253] Compared to Comparative Example 1, the biodegradable materials prepared in Examples 1-3 showed significantly more stable mechanical properties during accelerated aging at 50°C, indicating that the biodegradable materials have superior aging stability.

[0254] The performance tests of the biodegradable materials from Examples 1, 4, and 5 are shown in Table 2 below:

[0255] Table 2

[0256]

[0257] A comparison of Examples 1, 4, and 5 shows that:

[0258] (1) The more arms a macromolecular monomer has, the slightly lower the crystallinity of the biodegradable material and the gradually higher the gel content.

[0259] (2) The more arms a macromolecular monomer has, the higher the maximum tensile strength and the slightly lower the elongation at break.

[0260] (3) The more arms a macromonomer has, the slower the mass loss during the accelerated degradation process at 60°C. The mass loss ratio from slowest to fastest is: Example 1 < Example 4 < Example 5. That is, the more arms a macromonomer has, the slower the degradation rate.

[0261] (4) The more arms a macromolecular monomer has, the more stable its mechanical properties remain during the accelerated aging process at 50°C, and all of them are significantly better than the comparative example.

[0262] The performance tests of the biodegradable materials from Examples 1, 6, and 7 are shown in Table 3 below:

[0263] Table 3

[0264]

[0265]

[0266] The comparison between Examples 1 and 6 shows that, within a certain range, the arm length of macromolecular monomers has no significant impact on the performance of biodegradable materials.

[0267] As can be seen from the comparison between Example 1 and Example 7, when the arm length of the macromonomer is significantly shortened, the gel content will increase slightly, the mass loss during the accelerated degradation process at 60°C will be slower, and the mechanical properties will remain more stable during the accelerated aging process at 50°C.

[0268] The performance tests of the biodegradable materials from Examples 1, 8, and 9 are shown in Table 4 below:

[0269] Table 4

[0270]

[0271]

[0272] A comparison of Examples 1, 8, and 9 shows that:

[0273] (1) As the molecular weight of high molecular weight biodegradable polyester decreases, the crystallinity and gel content do not change significantly, the maximum tensile strength decreases significantly, and the elongation at break does not change significantly.

[0274] (2) As the molecular weight of high molecular weight biodegradable polyester decreases, the mass loss during the accelerated degradation process at 60°C is significantly faster. The mass loss ratio increases from slow to fast: Example 1 < Example 8 < Example 9. That is, the lower the molecular weight of high molecular weight biodegradable polyester, the faster the degradation.

[0275] (3) As the molecular weight of high molecular weight biodegradable polyester decreases, the stability of mechanical properties maintained during accelerated aging at 50°C is slightly improved.

[0276] The performance tests of the biodegradable materials of Examples 1, 10-12 and Comparative Examples 2-4 are shown in Table 5 below:

[0277] Table 5

[0278]

[0279]

[0280] As can be seen from the comparison of the above examples and comparative examples, the crosslinking temperature has a significant impact on the crosslinking reaction. At room temperature, light-induced crosslinking can only yield a very low gel content, resulting in significantly poor mechanical properties and aging stability. Crosslinking at higher temperatures (120℃~200℃) can significantly increase the degree of crosslinking (higher gel content), thereby improving mechanical properties and aging stability.

[0281] The cooling rate affects crystallinity. Within a certain range, the faster the cooling rate, the lower the crystallinity. At the same time, the mechanical strength of the material will decrease, the degradation rate will accelerate, and the aging stability will decrease.

[0282] The performance tests of the biodegradable materials from Examples 1, 13, and Comparative Example 1 are shown in Table 6 below:

[0283] Table 6

[0284]

[0285]

[0286] The comparison between Examples 1, 13, and Comparative Example 1 shows that the addition of small molecule crosslinking significantly increases the degree of crosslinking (gel content), but at the same time slightly reduces the crystallinity. Compared with Comparative Example 1, the biodegradable materials prepared in Examples 1 and 13 degrade faster and exhibit significantly better aging stability.

[0287] The performance tests of the biodegradable materials from Examples 1, 14, and 15 and Comparative Example 1 are shown in Table 7 below:

[0288] Table 7

[0289]

[0290] A comparison of Examples 1, 14, and 15 with Comparative Example 1 shows that the polyester degradation rates of the macromonomers in the examples are inconsistent. Theoretically, the degradation rates of the macromonomers from fastest to slowest are: DPE-PLG90 > DPE-PLG95 > DPE-PLC95. The corresponding biodegradable materials prepared show little difference in crystallinity and crosslinking degree, but their degradation rates differ, from fastest to slowest: Example 15 > Example 14 > Example 1. The aging performance and stability of the biodegradable materials in the examples are all superior to those in Comparative Example 1.

[0291] The performance tests of the biodegradable materials in Examples 1, 16-18 are shown in Table 8 below:

[0292] Table 8

[0293]

[0294] As can be seen from Examples 1 and 16-18, biodegradable materials can be prepared by using different initiators or initiation methods, and the relevant properties are similar.

[0295] The performance tests of the coronary stents in Example 19 and Comparative Example 7 are shown in Table 9 below:

[0296] Table 9

[0297]

[0298]

[0299] The comparison between the stents prepared in Example 19 and Comparative Example 7 shows that the crystallinity of the stents is similar. The gel content of the coronary stent in Example 19 is 48.6%, which is close to the gel content of the biodegradable material prepared in Example 1. The radial support force of the stent in Example 19 is slightly higher than that of the stent prepared in Comparative Example 7. The stent in Example 19 showed significant mass loss during the set 14-day accelerated degradation process, indicating that the degradation rate is faster.

[0300] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0301] The above-described embodiments are merely illustrative of several implementation methods of the present invention, facilitating a detailed understanding of the technical solutions of the present invention, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided by the present invention through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this invention patent should be determined by the content of the appended claims, and the specification and drawings can be used to interpret the content of the claims.

Claims

1. A biodegradable material, characterized in that, The biodegradable material has a chemical cross-linking network and a spherulite physical network. The content of the chemical cross-linking network of the biodegradable material is 20%~100%, and the crystallinity is 5%~50%. The content of the chemical cross-linking network of the biodegradable material refers to the mass content of gel in the biodegradable material. The raw materials for preparing the biodegradable material include: biodegradable polyester and macromolecular monomers, wherein the number average molecular weight of the biodegradable polyester is ≥100,000, and the macromolecular monomers include multi-arm biodegradable polyester prepolymers with end-group modified carbon-carbon double bonds. In the raw materials used for preparation, the biodegradable polyester accounts for 30% to 99% by mass, and the macromolecular monomer accounts for 1% to 70% by mass. The chemical crosslinking network includes a chemical crosslinking network formed by the crosslinking of the macromolecular monomers, a chemical crosslinking network formed by the covalent bonding of the macromolecular monomers and the biodegradable polyester, and a chemical crosslinking network formed by the covalent bonding of the biodegradable polyester. The spherulite physical network includes the spherulite network formed by the crystallization of the biodegradable polyester.

2. The biodegradable material according to claim 1, characterized in that, The raw materials used in the preparation meet one or two of the following conditions: (1) In the raw materials used in the preparation, the number-average molecular weight of the biodegradable polyester is 100,000 to 1,000,000; and (2) In the raw materials for preparation, the number of arms of the macromolecular monomer is 2 to 12, and the number average molecular weight of the single arm is 100 to 50,000.

3. The biodegradable material according to claim 2, characterized in that, The degradation cycle of the biodegradable material is between 1 month and 5 years, the tensile strength is between 20 MPa and 200 MPa, and the elongation at break is between 3% and 200%.

4. The biodegradable material according to any one of claims 1 to 3, characterized in that, The content of the chemical cross-linked network of the biodegradable material is 50%~90%, and the crystallinity is 20%~50%.

5. The biodegradable material according to claim 4, characterized in that, The raw materials used in the preparation meet one or two of the following conditions: (1) In the raw materials used for preparation, the biodegradable polyester accounts for 70% to 95% by mass and has a number-average molecular weight of 200,000 to 500,000; and (2) In the raw materials for preparation, the mass percentage of the macromolecular monomer is 5% to 30%, the number of arms is 2 to 6, and the number average molecular weight of the single arm is 5,000 to 20,000.

6. The biodegradable material according to claim 5, characterized in that, The degradation cycle of the biodegradable material is between 6 months and 3 years, the tensile strength is between 50 MPa and 180 MPa, and the elongation at break is between 3% and 50%.

7. The biodegradable material according to any one of claims 1-3 and 5-6, characterized in that, The biodegradable polyester and the multi-arm biodegradable polyester prepolymer are each independently selected from any one or more of poly-L-lactide, poly-D-lactide, polyglycolic acid, and poly-ε-caprolactone; or, the biodegradable polyester and the multi-arm biodegradable polyester prepolymer are each independently selected from copolymers formed by copolymerizing at least two monomers selected from D,L-lactide, D-lactide, L-lactide, glycolide, ε-caprolactone, δ-valerolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, butylene succinate, p-dioxanone, and trimethylene carbonate.

8. A method for preparing a biodegradable material, characterized in that, Includes the following steps: A biodegradable polyester, a macromonomer, and a first initiator are mixed and then subjected to a crosslinking reaction. The mixture is then cooled at a rate of 1°C / min to 50°C / min to below the glass transition temperature of the biodegradable polyester to prepare a biodegradable material. The temperature of the crosslinking reaction is between the crystallization temperature and the melting temperature of the biodegradable polyester. The biodegradable polyester has a number-average molecular weight ≥ 100,000, and the macromonomer includes a multi-arm biodegradable polyester prepolymer with end-group modified carbon-carbon double bonds; the biodegradable polyester has a mass percentage of 30%~99% based on the total mass of the biodegradable polyester and the macromonomer as 100%; the biodegradable material has a chemical cross-linking network and a spherulite physical network, the content of the chemical cross-linking network of the biodegradable material is 20%~100%, and the crystallinity is 5%~50%; the content of the chemical cross-linking network of the biodegradable material refers to the mass content of gel in the biodegradable material.

9. The method for preparing the biodegradable material according to claim 8, characterized in that, Based on the total mass of the biodegradable polyester and the macromonomer being 100%, the percentage of the first initiator in the total mass of the biodegradable polyester and the macromonomer is 0.05% to 5%.

10. The method for preparing the biodegradable material according to claim 8, characterized in that, The first initiator is a photoinitiator, and the crosslinking reaction step includes: irradiating with ultraviolet light at 120℃~200℃ for 1min~30min; or, The first initiator is a thermal initiator, and the crosslinking reaction step includes: carrying out the crosslinking reaction at 120℃~200℃ for 1min~30min; or, The crosslinking reaction steps include: performing an electron beam, X-ray, or γ-ray irradiation crosslinking reaction at 120℃~200℃ for 1min~30min.

11. The method for preparing the biodegradable material according to claim 8, characterized in that, The cooling rate is 5℃ / min to 20℃ / min.

12. The method for preparing the biodegradable material according to any one of claims 8 to 11, characterized in that, In the step of mixing the biodegradable polyester, macromonomer and first initiator, a crosslinking agent is also added. The crosslinking agent is a compound or oligomer containing at least two double bonds, and the number average molecular weight of the oligomer is 200 to 5000.

13. The method for preparing the biodegradable material according to claim 12, characterized in that, The crosslinking agent satisfies any one or two of the following conditions: (1) The crosslinking agent is selected from any one or two of trimethylolpropane trimethacrylate, tetra-arm polyethylene glycol acrylate, polyethylene glycol diacrylate, ethylene glycol diallyl ether, pentaerythritol triallyl ether, trimethylolpropane diallyl ether, butanediol divinyl ether, diethylene glycol divinyl ether, and triethylene glycol divinyl ether; and (2) The mass of the crosslinking agent is 0.05% to 10% of the total mass of the biodegradable polyester and the macromolecular monomer.

14. The method for preparing the biodegradable material according to any one of claims 8-11 and 13, characterized in that, The macromolecular monomer is prepared by the following steps: Under the conditions of a catalyst and a second initiator, the monomers of the multi-arm biodegradable polyester prepolymer are subjected to ring-opening polymerization to prepare the multi-arm biodegradable polyester prepolymer, wherein the second initiator is a polyhydroxy compound. The macromonomer is prepared by reacting the multi-arm biodegradable polyester prepolymer with a substance containing carbon-carbon double bonds and a group capable of reacting with hydroxyl groups, wherein the group capable of reacting with hydroxyl groups is selected from any one or more of acid anhydrides, acyl chlorides, isocyanates and epoxy groups.

15. The method for preparing the biodegradable material according to claim 14, characterized in that, The preparation steps of the macromonomer satisfy any one or more of the following conditions: (1) The second initiator accounts for 0.05% to 10% of the molar percentage of the constituent monomers of the multi-arm biodegradable polyester prepolymer; (2) The number of hydroxyl groups in the second initiator is 2 to 6; (3) The polymerization reaction time is 12h~96h; and (4) The substance containing carbon-carbon double bonds and a group capable of reacting with hydroxyl groups is selected from any one or more of methacrylic anhydride, methacryloyl chloride, isocyanate ethyl methacrylate, glycidyl methacrylate, ethyl isocyanate acrylate, acrylic anhydride, acryloyl chloride, propylene oxide acrylate and allyl glycidyl ether.

16. The application of a biodegradable material in the preparation of biodegradable scaffolds, cardiac occluders, surgical sutures, drug-release coatings, tissue packing materials, bone repair products, or food packaging materials, characterized in that, The biodegradable material is the biodegradable material according to any one of claims 1 to 7 or the biodegradable material prepared by the preparation method of the biodegradable material according to any one of claims 8 to 15.

17. A biodegradable stent, characterized in that, The material of the biodegradable scaffold includes the biodegradable material according to any one of claims 1 to 7 or the biodegradable material prepared by the preparation method of the biodegradable material according to any one of claims 8 to 15.

Citation Information

Patent Citations

  • Modified polylactic acid degradable stent and preparation method thereof

    CN103709386A

  • Biodegradable cross-linked polymer, and preparation method thereof

    CN103709691A